Stay calm and focus on the learning outcomes: Tools for taking biophysical chemistry online. Issue 5 (15th August 2020) - Ballester, Maria; Van Hoozen, Brian; Sikora, Arthur K.
Abstract: Course specific learning outcomes are an important tool to define the scope of a course and can be very helpful when designing experiments and assessments. With slight modification, these learning outcomes can serve as a guide when transitioning to the distance learning format especially in courses with a traditional lab. Here we present such an example for the biophysical chemistry course.